ANALYSIS OF PERMISSIVE PARENTING PATTERNS ON THE SOCIAL-EMOTIONAL DEVELOPMENT OF 5-6 YEAR OLD CHILDREN AT MIFTAHUT THOLIBIN KINDERGARTEN - Nur Hasanah; Aries Dirgayunita (Al-Mubin, 2026)
This study aims to explain how parents apply permissive parenting styles and analyze their impact on the social-emotional development of 5-6-year-old children at Miftahut Tholibin Kindergarten, Probolinggo. The study used a qualitative approach with a multiple case study design. The research informants consisted of three parents who were identified as using permissive parenting. Data were acquired through observation, interviews, and documentation, then analyzed inductively. The results showed that permissive parenting was characterized by giving children broad freedom to make decisions, weak house rules, and minimal supervision and consequences. This condition has an impact on children, such as difficulty regulating emotions, a tendency to act impulsively, lack of discipline, and obstacles in establishing relationships with peers. Although the emotional warmth of parents is quite high, permissive parenting hinders the formation of children's independence and social responsibility. These findings indicate the need for a balanced parenting style that provides emotional support while establishing consistent rules so that children's development can proceed optimally